Comparative Analysis of Verbalization of Conceptual Semantics of Hyperbola in Different System Languages and their Linguculturological, Pragmatic Importance - Hamidov Nodirbek (Zien Journals, 2022)
this article gives information about comparative-typological analysis of verbal tools with semantic meaning of hyperbola given in different languages and their structural-semantic, linguo-cognitive, communicative-pradmatic and linguoculturological meanings that give a classification of aspects and comparison in relation to distinguish their meanings from each other.
Keywords: verbal tools; linguocultorolgy; concept; hyperbola